In vitro culture of mollusc hemocytes. Functional study of burst respiratory activity and analysis of interactions with protozoan and procaryotic pathogens - Boulo, Viviane; Hervio, Dominique; Morvan, Annie; Bachere, Evelyne; Mialhe, Eric (Actes du colloque, 8th International Conference on Invertebrate and Fish tissue culture. Tissue culture association, Comubia : pp 56-64, 1991)
The chief importance of hemocytes as immune effectors in molluscs has led to develop researches for in vitro culture. The chemiluminescence technique has been used to estimate the phagocytosis capacity of Crassostrea gigas hemocytes according to different culture media and times. Sea water was used as a basic medium. Additives, such as antibiotics or glucose and buffers, such as Tris or Hepes, were tested as weIl as artificial sea water. Hemocyte chemiluminescence activities were recorded at t=o in relation to the medium composition. The highest values were observed when hemocytes were kept in sea water without any modification. Whichever medium, chemiluminescence activity was substantially decreased when hemocytes were previously kept in vitro for a few hours. Thus, chemiluminescence technique could be a well-adapted method to estimate the functional capacity of mollusc hemocytes and to study medium composition in prospect of long-term molluscan cell cultures. Despite present limitations of short-term hemocyte primary cultures, they were used to study in vitro the interactions between hemocytes and some mollusc-specific pathogens. The hemocyte recognition and entry mechanisms of Bonamia ostreae (Protozoa: Ascetospora), an intrahaemocytic parasite of fIat oyster Ostrea edulis, were investigated. Moreover, it was demonstrated that hemocyte respiratory burst was not triggered during parasite phagocytosis. Similar experiments were performed with St-Jacques scallop (Pecten maximus) hemocytes and a host-specifie gill Rickettsialeslike organism, leading to evidenee some pathogen adaptation for escaping host-immune response. These first in vitro models extrapolated to other pathogens anti-infectious immune response of molluscs.